Accuracy Assessment of Open-Source DEM: A Case for Nepal - Dahal, Tanka Prasad; Dangol, Susheel (Journal on Geoinformatics, Nepal, 2025)
Digital representation of the earth topography is called Digital Elevation Model (DEM). DEMs are very useful for disaster assessment, 3D modelling, infrastructure planning and other development activities. There are various satellite systems providing the DEMs with different spatial resolution freely. This study assesses the reliability of the freely available DEMs while using those data for decision making. Reference elevation point data are taken from the topographical base map of the respective area. Statistical calculation was carried out for the testing reliability of the data. Root Mean Square Error (RMSE), Standard Deviation and Mean deviation are calculated to conduct the accuracy assessment. From the study, it is seen that, ALOS PRISM DEM of 30m resolution gave the precise result based on RMSE with the value of 5.9m in comparison to other five DEMs used in this study.